Empowering Minds in the Hospitality Sector: The Moderation-Mediation Role of Psychological Empowerment in Fostering Transformational Leadership and Psychological Well-being - Hasanein, Ahmed Mohamed; Elrayah, Musaddag (Journal of Posthumanism, 2025)
Due to the absence of transformational leadership and effective management practices, the working conditions in the hospitality sector can be challenging, impacting job satisfaction, quality of life, and psychological well-being of hospital workers. Few writers have examined the elements that influence psychological well-being, like transformational leadership. This study examines the direct impact of psychological empowerment and transformational leadership on employees' psychological well-being in the Saudi hotel industry, using self-determination theory as a foundation. The research also examines the dual role of psychological empowerment as a mediator and moderator in the relationship between transformational Leadership and psychological well-being. A purposive sample of 476 frontline employees in five-star hotels located in the Eastern Region of Saudi Arabia was surveyed via an online survey. The partial least squares structural equation modeling (PLS-SEM) was used to test the proposed model. The findings indicate a large positive effect of transformational Leadership on psychological empowerment and psychological well-being. Additionally, there exists a key mediating role of psychological empowerment for the transformational Leadership – psychological well-being relationship, and there is an important moderating impact. This study's findings have significant implications for hotel management in terms of promoting psychological empowerment to enhance workers' well-being and enhance organizational effectiveness and service standards in the hospitality industry.